Efektivitas implementasi teknologi kecerdasan buatan (AI) dalam pembelajaran matematika tingkat menengah - Nuryami, Nuryami; Hotim Nurjannah; Nurhasanah, Nurhasanah (IKIP Siliwangi, 2026)
Despite the rapid development of artificial intelligence (AI) technology in education, few studies have integrated these findings into a systematic synthesis to identify patterns, opportunities, and challenges of AI implementation. This study aims to fill this gap through a Systematic Literature Review (SLR) approach by analyzing five selected scientific articles from 2014–2024 relevant to the use of AI in junior high and senior high schools. The results show that AI technologies, such as ChatGPT, adaptive learning systems, and intelligent pedagogical agents, can improve learning personalization, student engagement, and understanding of complex mathematical concepts. However, their implementation still faces various challenges, including limited infrastructure, low teacher technological literacy, and ethical and privacy issues. Research trends over the past five years have shown a significant increase in AI integration, particularly through adaptive approaches and game-based learning. These findings provide a basis for developing more effective and contextual AI implementation strategies in mathematics learning.